ATOPIC DERMATITIS IN SHIH-TZU: CASE REPORT - Lopes, Maria Eduarda Ramalho; Santos, Brisa Lafeta Rabelo; Fonseca, Maria Cecilia Silva; de Souza, Ivete Mariana Pereira; Fonseca, Maria Cecilia Silva; Gusmão, Emerson Márcio; da Silva, Matheus Pereira; Siqueira, Juliano Santos; Costa, Renê Ferreira; Pires Neto, Otaviano de Souza; Pires, Daniel Ananias de Assis; Moura, Marielly Maria Almeida; et al. (Seven Editora, 2025)
Canine atopic dermatitis (CAD) is a chronic, immune-mediated, multifactorial inflammatory disease that represents one of the main challenges in veterinary dermatology. It is characterized by an intense immune response to environmental allergens, associated with skin barrier dysfunction and genetic predisposition. Clinical signs include persistent pruritus, erythema, alopecia, and secondary infections, with individual variations in disease presentation and progression. Diagnosis is clinical, based on the exclusion of other pruritic dermatoses and the use of specific criteria, aided by complementary exams. Treatment requires a multimodal approach, including immunomodulatory agents, topical care, hypoallergenic diets, and environmental control. Continuous management and owner compliance are essential to maintain the patient’s quality of life. New therapies are being studied, reinforcing the importance of ongoing veterinary training. DOI: https://doi.org/10.56238/sevened2025.029-096